Na2CO3-Catalyzed N-Acylation of Indoles with Alkenyl Carboxylates - Zhou, Xiao-Yu; Chen, Xia (Synthesis, 2019)
The N-acylation of indoles has been accomplished via inorganic base catalysis. It provided an efficient and simple catalysis system for the preparation of N-acylindoles with alkenyl carboxylates as acylating agents. A broad variety of indoles undergo the smooth N-acylation using Na2CO3 as catalyst in MeCN at 120 °C to give the corresponding N-acylindoles in good to excellent yields.
Keywords: inorganic base; catalysis; acylation; indole; alkenyl carboxylates